(untitled) (International Seven Journal of Multidisciplinary, 2025)
The study investigated determinant factors related to mental health in Federal Institutions of Higher Education and proposed a preventive model. A quantitative, descriptive-analytical methodology was used, through questionnaires applied to technical-administrative professionals in education in the area of occupational safety. The objective is to evaluate the impact of working conditions on the mental health of federal employees, and administrative technicians in education and propose preventive actions. The results pointed to a high incidence, in certain categories, of mental and emotional disorders, evidencing the need for effective public health policies. The implementation of an institutional informative website was well evaluated, demonstrating its potential as a preventive tool. It is concluded that the use of strategies with digital tools and multidisciplinary approaches is essential to promote mental health and improve the quality of life of civil servants, suggesting the expansion of initiatives to other institutions.